(untitled) (Journal of Human Sciences, 2021)
This research aims to reveal the difficulties and obstacles that researchers face when conducting and preparing research and scientific studies. It also aims to stand on the reality of scientific research in Libya and to identify the best solutions and strategies to overcome challenges and obstacles. The research reached a number of conclusions :- -There are a number of difficulties facing scientific research, some of which are due to subjective factors related to the researcher, including administrative factors, and there are factors related to funding for research, as well as factors attributed to the nature of the scientific specialization . -Scientific research in Libya needs efforts to illustrate the difficulties, and to look at research adequacy aimed at solving problems in society and addressing negative phenomena and a step to improve the educational process and upgrade it . -One of the most important strategies that can be taken to overcome difficulties is the concerted efforts of all parties concerned with scientific research, the researcher, the institution he follows, and the society with its centers and institutions.